THE EFFECT OF COMPETENCY, DISCIPLINE, AND ATTITUDE TOWARD EMPLOYEES’ PERFORMANCE AND ITS IMPLICATIONS ON THE PERFORMANCE OF ACEH TRANSPORTATION DEPARTMENT - Asmawati; Edwar M Nur; Irwan Safwadi; Nurin Fahira (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
The Department of Transportation Office has a significant role in improving quality transportation services in the regions because it is related to public services in the transportation sector. This study aims to determine the effect of competence, work discipline, work attitudes, and employees' performance and its implications on the performance of the Transportation Department in Aceh. The sample in this study is 157 respondents analyzed using the Structural Equation Modeling (SEM) method. The results show that competence, work discipline, and work attitude have the positive and significant effects on the employees' performance. Moreover, the findings also reveal an actual fact that competence, work discipline, and work attitude have a positive and significant effect on the performance of the Aceh Transportation Department. However, there is an indirect effect of competence, work discipline, and work attitude toward employees performance in Aceh Transportation Department. The study holds important implications for both theory and practice.